Improving Participant Satisfaction through the Quality of BPJS Ketenagakerjaan Services: A Community Service Program at Yoga Barn Ubud: English - Anak Agung Natsumi Kusumaputri; Komang Widhya Sedana Putra P (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
In today’s global economic era, labor plays a pivotal role in trade and economic development, necessitating both protection and enhancement. As outlined by Law No. 40 of 2004 and Law No. 24 of 2011, BPJS, a non-profit agency, is set to replace PT Askes Indonesia and PT Jamsostek in managing national social insurance. BPJS Ketenagakerjaan provides crucial programs such as Old Age Insurance, Work Accident Insurance, and Death Insurance to ensure comprehensive protection for employees. This research is designed to evaluate the impact of these employment social security programs on the satisfaction of Yoga Barn Ubud participants. The study employs a combination of outreach activities and surveys to gather data. Socialization efforts include the development of informational materials, the scheduling and execution of educational sessions, and the distribution of surveys to gauge participant feedback. The findings reveal that BPJS Employment social protection is highly valued by Yoga Barn employees. The main objective of this research is to enhance understanding and increase participation in the BPJS Ketenagakerjaan program. By providing detailed insights into the effectiveness of the social security measures, the study aims to support improved engagement and satisfaction among employees at Yoga Barn Ubud.